2014
DOI: 10.12659/msm.890714
|View full text |Cite
|
Sign up to set email alerts
|

Is experimentally induced pain associated with socioeconomic status? Do poor people hurt more?

Abstract: BackgroundThe association of pain and socioeconomic status is widely reported, yet much less clearly understood. The aim of this study was to investigate the association of experimentally induced pain threshold and tolerance with socioeconomic status.Material/MethodsThe study sample consisted of 319 adult subjects from the population of the island of Vis, Croatia, which was previously shown to have a high level of social homogeneity. A manual dolorimeter was used to measure mechanical pressure pain threshold (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The validity of our results depended upon the unbiased and accurate self-reporting of symptoms and sickness absence among cases. If those of lower SES perceived their symptoms differently to those of higher SES, which has been observed in studies investigating perceptions of pain across socioeconomic groups [ 35 , 36 ], our results could be a mere artefact of the severity measurement. Nonetheless, the variables used to derive the symptom severity score in our study were related to the presence and duration of symptoms, which are rather more objective measures of severity compared to, for example, a subjective rating of symptom severity from mild to severe.…”
Section: Discussionmentioning
confidence: 64%
“…The validity of our results depended upon the unbiased and accurate self-reporting of symptoms and sickness absence among cases. If those of lower SES perceived their symptoms differently to those of higher SES, which has been observed in studies investigating perceptions of pain across socioeconomic groups [ 35 , 36 ], our results could be a mere artefact of the severity measurement. Nonetheless, the variables used to derive the symptom severity score in our study were related to the presence and duration of symptoms, which are rather more objective measures of severity compared to, for example, a subjective rating of symptom severity from mild to severe.…”
Section: Discussionmentioning
confidence: 64%
“…The findings are consistent with previous studies. Researches had indicated that the higher risk of pain is correlated with lower sociodemographic status [7, 9, 28]. As it reported by National Bureau of Statistics of China, the average monthly income of Chinese was 2165 Yuan (318 USD) in 2017 and lower in rural area [29].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Jin et al ( 2004 ) conducted a cross-sectional study in China and found that garment workers had a higher annual prevalence of lower back pain (74 %) than teachers (40 %) (PR 1.9, 95 % CI 1.4–2.4); this could be explained by the garment workers’ long duration of sedentary positions. Miljković et al ( 2014 ) investigated the association of experimentally induced pain threshold and tolerance with socioeconomic status, and their results suggested that poor people have a higher prevalence of pain. A significant association was found between the experimentally induced pain threshold and tolerance and marital socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%